Pengaruh Capital Intensity, Thin Capitalization, dan Profitability terhadap Tax Avoidance Emiten Consumer Non-Cyclicals Bursa Efek Indonesia Periode 2019-2023 - Siti Maisa Zahara; Amor Marundha; Maidani Maidani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to test and analyze the effect of capital intensity, thin capitalization, and profitability on tax avoidance. The research method uses quantitative research. Types and sources of data in research with the audit reports of non-cyclical consumer issuers on the Indonesia Stock Exchange for the 2019-2023 period. The sampling technique used was purposive sampling method and obtained 170 observations. Data processing in this study using Eviews 13. It can be concluded that capital intensity has a positive and significant effect on tax avoidance, thin capitalization has a negative but insignificant effect on tax avoidance, and profitability has a negative and significant effect on tax avoidance.